CASE: Managing customer relationship gaps at SKF - Fredrik Nordin; Danilo Brozovic; Christian Kowalkowski; Mats Vilgon (jbm - Journal of Business Market Management, 2015)
This teaching case study focuses on SKF, a leading supplier of products, services and solutions. It consists of an overview of the company and then a narrative concentrating on the sudden loss of a large customer relationship. Moreover, it explores how central individuals devise various strategies to recover the relationship. The purpose is to stimulate a discussion concerning alternative ways for handling such relationship losses. The case is especially suited as a starting point for discussions of different marketing strategies and customer relationship tactics. Teaching notes are provided with discussion questions and possible answers.
urn:nbn:de:0114-jbm-v8i2.1108
Keywords: 650; Service; Disintermediation; Industrial marketing; Intermediaries; Servitization; Solutions